Design of the Argonne Low Power Reactor (ALPR) - Hamer, Eberhard E., editor.; Argonne National Laboratory. (Argonne, Ill. : Argonne National Laboratory, Reactor Engineering Division, 1961)
A description is given of the design of a prototype "packaged" nuclear power plant. The purpose of the plant is to alleviate fuel oil logistics and storage problems posed by remote auxiliary DEW Line radar stations north of the Arctic Circle. The ALPR (redesignated SL-1) is a 3 Mwt, heterogeneous, highly enriched uranium- fueled, natural-circulation boiling water reactor, cooled and moderated with light water. Steam at 300 psig, dry and saturated (421 deg F) is passed directly from the reactor to a conventional turbine-generator to produce electric power (300 kw nominal) and space-heating (400 kw) requirements consistent with rigid mechanical and structural specifications prescribed by the military, and dictated by the extreme geophysics prevailing at the ultimate site. The over-all design criteria emphasize: simplicity and reliability of operation and maintenance, with minimum supervision; minimum on-site construction; maximum use of standard components; limited water supply; utilization of local gravel for biological shielding; transportability by air lift; and nominal 3-year fuel operating lifetime per core loading. Other authors/contributors include: N. R. Grant, H. H. Hooker, G. L. Jorgensen, W. J. Kann, W. C. Lipinski, G. C. Milak, A. D. Rossin, D. H. Shaftman, A. Smaardyk, M. Treshow. E. E. Hamer, Editor and Project Coordinator. "Operated by the University of Chicago under Contract W-31-109-eng-38." At head of title: Argonne National Laboratory. "May 1961." Includes bibliographical references. References. pp. 266. Appendix 5. Technical characteristics of Argonne Low Power Reactor (ALPR). pp. 257. Appendix 4. Aluminum-nickel alloy corrosion testing. pp. 251. Appendix 3: Biological gravel shielding. pp. 247. Appendix 2: Reactor thermal analysis. 242. Appendix 1: Evolution of the reactor core design and reactor physics characteristics of the Fresh Reference 3-Mwt system. pp. 213. Reactor and power plant instrumentation and control systems. pp. 178. Electrical generation and distribution system. pp. 164. Power plant components. pp. 141. Fuel-handling system. pp. 119. Shielding. pp. 113. Reactor plant auxiliaries. pp. 103. Reactor components. pp. 67. Operational characteristics. pp. 51. Design summary. pp. 39. Site and buildings. pp. 26. Introduction. pp. 17. A description is given of the design of a prototype "packaged" nuclear power plant. The purpose of the plant is to alleviate fuel oil logistics and storage problems posed by remote auxiliary DEW Line radar stations north of the Arctic Circle. The ALPR (redesignated SL-1) is a 3 Mwt, heterogeneous, highly enriched uranium- fueled, natural-circulation boiling water reactor, cooled and moderated with light water. Steam at 300 psig, dry and saturated (421 deg F) is passed directly from the reactor to a conventional turbine-generator to produce electric power (300 kw nominal) and space-heating (400 kw) requirements consistent with rigid mechanical and structural specifications prescribed by the military, and dictated by the extreme geophysics prevailing at the ultimate site. The over-all design criteria emphasize: simplicity and reliability of operation and maintenance, with minimum supervision; minimum on-site construction; maximum use of standard components; limited water supply; utilization of local gravel for biological shielding; transportability by air lift; and nominal 3-year fuel operating lifetime per core loading. Mode of access: Internet. digitized